Optimasi Ekstraksi Triterpenoid Total Pegagan (Centella asiatica (Linn.) Urban) yang Tumbuh di Riau - Mora, Enda; Fernando, Armon (Jurnal Penelitian Farmasi Indonesia, 2013)
Optimization of extraction of total triterpenoid content from pegagan (Centela asiatica (Linn) Urban) originated from three locations inRiau province; kecamatan Siak Hulu, kabupaten Kampar, kecamatan Belilas, kabupaten Pelalawan and kecamatan Tampan kota Pekanbaruwas carried out using soxhlet method. n-Hexane and methanol were used as eluent and 8 grams of active carbon as adsorbent. The resultrevealed that pegagan originated from kabupaten Kampar showed the highest yield with total triterpenoid content of 3.94%, while otherspegagan afforded lower yield; 1.25% for kabupaten pelalawan and 1.91% for kota Pekanbaru.